PENGARUH FREE CASH FLOW, PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2016 - Rawiyatul Hasana; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACTThere is always a conflict between shareholders and management within the company, namely in making decisions to distribute dividends to shareholders. It is necessary to pay attention to several factors that can influence the dividend distribution policy. Ratio analysis can be used as an alternative to test these factors. This study aims to determine how much factors Free Cash Flow (FCF), Profitability (ROI), Liquidity (CR), and Leverage (DER) affect the Dividend Policy (DPR). The sample in this study consisted of 12 food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2014-2016 period. The sample in this study uses purposive sampling method. The analytical tool used in this study is multiple linear regression. Based on the results of the study showed that the variable Free cash flow and profitability had a negative effect not significant on dividend policy, while liquidity and leverage had a significant positive effect on dividend policy. Keywords: Free Cash Flow, Profitability, Liquidity, Leverage and Dividend policy